1991
DOI: 10.4012/dmj.10.172
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sealed Cup Yoke Type Dental Magnetic Attachment

Abstract: The purpose of this study was to develop a small cup type yoke magnetic attachment sealed from oral 341 gf on average.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 10 publications
0
22
0
2
Order By: Relevance
“…A smaller attachment size is also of greater benefit for esthetic adaptability and constrained space applications [8][9][10] . Different designs of keeper and magnetic assembly have been developed to reduce attachment size and provide optimum attractive force for useful retention 11,12) . Different designs have been shown to vary in magnetic circuit and retention strength.…”
Section: Introductionmentioning
confidence: 99%
“…A smaller attachment size is also of greater benefit for esthetic adaptability and constrained space applications [8][9][10] . Different designs of keeper and magnetic assembly have been developed to reduce attachment size and provide optimum attractive force for useful retention 11,12) . Different designs have been shown to vary in magnetic circuit and retention strength.…”
Section: Introductionmentioning
confidence: 99%
“…Dental magnetic attachments are generally composed of either a pair of magnets, or a magnet and a magnetic alloy 1,2) . In either instance, the attractive force generated between this pairing acts to retain dentures or the superstructures of dental implants in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…To complete the magnetic circuit, a shield ring of austenitic stainless steel (SUS 316 or SUS 316L) is laser welded in the boundary between the cup and the disk yoke 1) . Although ferritic stainless steels have corrosion resistance better than that of SUS 316L, an alloy which is widely used for surgical implants 7,8) , the keepers are embedded in the precious alloys used for root cap clinical treatment by casting or cementing 9) .…”
Section: Introductionmentioning
confidence: 99%
“…Saygili and Sahmali 2) even reported that the retentive force of precision attachments decreased depending on the wear of female and male parts, while the magnetic retainers' retention increased over time and use according to the induction of magnetic fields. A dental magnetic attachment is usually composed of a magnet encapsulated in a cup yoke made of ferritic and austenitic stainless steels and a keeper made of ferritic stainless steel 3) . The magnet is normally embedded in a denture, and the keeper is fixed on a root cap made of noble metal alloy by cast bonding or cementation.…”
Section: Introductionmentioning
confidence: 99%